Intrahepatic Cholestasis of Pregnancy with Severe Elevation of Bile Acids in the Setting of Acute Hepatitis C Infection - Megan L. Lawlor; Agatha S. Critchfield (Case Reports in Obstetrics and Gynecology)
Intrahepatic cholestasis of pregnancy (ICP) is a complication of pregnancy resulting in elevation of serum bile acid levels. ICP is often associated with underlying liver disease, including hepatitis C. Bile acids in relationship to the acute infection of hepatitis C virus have not yet been delineated in the literature. A 26-year-old gravida 4 para 2103 with dichorionic, diamniotic twin gestation and history of intravenous drug abuse developed ICP in the setting of acute hepatitis C infection. In addition to clinical symptoms of pruritus and right upper quadrant pain, she developed severe elevation in bile acids, 239 micromol/L, and transaminitis aspartate aminotransferase 1033 U/L, and alanine aminotransferase 448 U/L. She received ursodeoxycholic acid and antenatal testing was performed. Patient delivered vaginally at 33-week gestation following preterm rupture of membranes. Neonates were admitted to NICU and had uncomplicated neonatal courses. In the setting of ICP with significant transaminitis and severe elevation of bile acids, consideration of acute viral hepatitis is important, especially considering the worsening opioid epidemic and concurrent increase in intravenous drug use in the United States. Further study is needed regarding the acute form of HCV infection and its effect on ICP and associated bile acids.